2003
DOI: 10.1034/j.1600-048x.2003.03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural plumage colour and parasites in satin bowerbirdsPtilonorhynchus violaceus: implications for sexual selection

Abstract: Doucet, S. M. and Montgomerie, R. 2003. Structural plumage colour and parasites in satin bowerbirds Ptilonorhynchus 6iolaceus: implications for sexual selection. -J. Avian Biol. 34: 237-242.We investigated whether variation in structural plumage coloration in satin bowerbirds, Ptilonorhynchus 6iolaceus, could reveal the intensity of infection from parasites, as predicted from models of parasite-mediated sexual selection (PMSS). To do this, we captured adult male, female, and juvenile male satin bowerbirds in Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 23 publications
4
43
2
3
Order By: Relevance
“…Investigations of colouration as honest signals of quality have focused primarily on pigment-based colouration (Hamilton & Zuk 1982;Lozano 1994;Olsen & Owens 1998;Hill 1999;McGraw & Hill 2000;Grether et al 2001;Blount et al 2003), but structural colours are being studied with increasing frequency from this perspective ( Johnsen et al 1998( Johnsen et al , 2003Keyser & Hill 1999;McGraw et al 2002;Doucet & Montgomerie 2003;Siefferman & Hill 2003). Most animal colours, however, are generated through a combined effects of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of colouration as honest signals of quality have focused primarily on pigment-based colouration (Hamilton & Zuk 1982;Lozano 1994;Olsen & Owens 1998;Hill 1999;McGraw & Hill 2000;Grether et al 2001;Blount et al 2003), but structural colours are being studied with increasing frequency from this perspective ( Johnsen et al 1998( Johnsen et al , 2003Keyser & Hill 1999;McGraw et al 2002;Doucet & Montgomerie 2003;Siefferman & Hill 2003). Most animal colours, however, are generated through a combined effects of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The plumage colouration of tree swallows is structural-based, and evidence is accruing for the condition-dependence and thus honest-signaling potential of structural plumage colouration in birds (Hill 2006b). To date, most studies examining structural plumage colouration have found that plumage brightness and UV-blue colouration are reduced in individuals that suffer from nutritional stress (Siefferman and Hill 2005a) and parasitic infection (Doucet and Montgomerie 2003), and that less colourful, duller individuals have lowered reproductive success (Siefferman and Hill 2005a;Doutrelant et al 2008). I found that more UV-blue, brighter females had higher levels of parasitism ( contrary to what would be expected if only high quality individuals can produce these potentially costly plumage traits (Zahavi 1975;Hamilton and Zuk 1982;Kodric-Brown and Brown 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Developmental perturbations, however, may cause variation in the number or thickness of the feather nanostructures and could affect the brightness and colour of the feather (Prum 2006). In fact, studies have found that variation in the hue and brightness of structurally-coloured feathers is related to the nutritional status (Keyser and Hill 1999) and physiological condition of the bearer (Doucet and Montgomerie 2003). If these nanostructures are costly to produce (Shawkey et al 2003;Doucet et al 2006), this may be the physiological mechanism allowing structural plumage colouration to be an honest indicator of individual quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding all factors that may drive the attractiveness of males, individuals that have better external and physical conditions will compete more efficiently for females (Kirkpatrick & Ryan 1991). Ectoparasites signalize the current health condition of birds, and affect negatively the fitness of males by increasing the cost of antiparasite effects in their immune system, causing loss of blood, infections, and diseases (Price 1980, de Lope et al 1993, Doucet & Montgomerie 2003. Additionally, females are able to enhance the viability of their offspring by choosing males with better physical conditions as an indicator of relative resistance to parasites (Hamilton & Zuk 1982).…”
Section: Discussionmentioning
confidence: 99%